Differences in the Application of STAD and NHT Cooperative Learning Models on Mathematics Learning Outcomes Assessed from Self-Efficacy Students of State Junior High School 18 Palu - Rahmayanti, Henita; Ismaimuza, Dasa; Rochaminah, Sutji (Universitas Tadulako, 2018)
This research was intended to get a clear description of the difference learning result in relation to student self-efficacy by applying the cooperative learning model types of student teams achievement division and numbered head together. The research design was a quantitative approach. The sample of this research was students of SMP Negeri 18 Palu, Grade VIIA and VIIB as the first experiment classes and the second experiment classes were VIID and VIIE. This research applied an experimental method with a factorial design was 2 x 3. The research instruments administered to collect data, questionnaire of self-efficacy, and test for the students’ results of learning. Data analyzed used test Anova two lines and test t-Scheffe. The findings of the research were (1) there was a difference of students’ result in learning mathematic by applying student teams achievement division (STAD) and numbered head together (NHT); (2) there was a difference of students’ result in learning mathematics to students who have high Self-efficacy, middle self-efficacy, and low Self-efficacy; (3) there was no interaction between learning cooperative model with self-efficacy in relation with the result of students in learning mathematics; (4) there was a difference of students’ result in learning mathematics by applying student teams achievement division (STAD) and numbered head together (NHT), especially to high self-efficacy, middle self-efficacy, as well as low self-efficacy.